The prognostic value of peripheral hematological biomarkers in patients with hypersensitivity pneumonitis: A single-center retrospective study - Mammadova, Ayshan; Yalçınkaya, Zeynep; Yılmaz Demirci, Nilgün; Türktaş, Haluk (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2025)
Background/aim: Investigating inflammation-related biomarkers in hypersensitivity pneumonitis (HP) patients may provide valuable insights, particularly in determining their clinical course and prognosis. This study aimed to explore the potential role of peripheral hematological biomarkers in predicting the clinical course and prognosis of HP patients.Materials and methods: This retrospective study included 75 patients diagnosed with HP. Demographic data, symptoms, exposure history, pulmonary function tests, systemic immune-inflammation index (SII), and aggregate index of systemic inflammation (AISI) were analyzed.Results: Elevated SII (1353.6±915.15) and AISI (1001.1±695.38) values were significantly higher in patients with fibrotic HP compared to non-fibrotic HP (SII: 607.84±334.53, AISI: 375.01±235.18) (p